Validating quality standards in Palestinian emergency departments: An e-Delphi survey approach - Abed Alr’oof Bani Odeh; Lee Wallis; Motasem Hamdan; Willem Stassen (PLoS ONE, 2025)
To validate Palestine’s previously derived emergency department quality standards (EDQS) using an e-Delphi survey. A two-round e-Delphi survey validated the EDQS, developed in an earlier study through a literature review and consensus-building among Palestinian emergency medicine and healthcare quality experts. The study purposively sampled 53 emergency department and healthcare quality experts with over 5 years of experience. A Likert scale was used to rate the standards on readability, clarity, and comprehensiveness in the initial round to reach consensus on the EDQS, with detailed feedback. An expanded expert group refined the shortlisted standards in the next phase. Lime Survey collected data anonymously. A set of 100 EDQS was validated through a two-round e-Delphi survey. In the initial round, 103 standards were presented, and consensus was achieved, resulting in a refined list of 100 standards. Among these, 39 standards fell under the clinical pathway domain, and 61 under the administrative pathway domain. In the second round, the validity of these standards was affirmed, with 96.4% consensus for clinical standards and 97.3% for administrative standards. Additionally, seven subdomains of EDQS were associated with the clinical pathway domain: triage, treatment, transportation, medication safety, patient flow, and medical diagnostic services, and nine subdomains were linked to the administration pathway domain: documentation, information management systems, access-location, design, leadership, management, workforce staffing, training, equipment, supplies, capacity-resuscitation rooms, resources for a safe working environment, performance indicators, and patient safety-infection prevention and control programs. The study validated context emergency department quality standards in Palestine, with over 97% consensus indicating a commitment to quality care. Experts suggest further research on implementation feasibility. Validated standards can aid healthcare leaders in resource allocation, staff training, and enhancing patient care, potentially leading to significant improvements in emergency healthcare in Palestine.